I have to prove that for $(x_1,y_1),(x_2,y_2)\in[0,1]^2$ $$|x_1y_1-x_2y_2|\leq|x_1-x_2|+|y_1-y_2|$$ Now what I do is this:

w.l.o.g. say $y_1<y_2$. Def $$f(y)=y(\frac{x_1-x_2}{y_1-y_2}(y-y_2)+x_2)$$ So that $$|x_1y_1-x_2y_2|=|f(y_1)-f(y_2)|$$ So to use the mean value theorem:


So for some $\gamma\in (y_1,y_2)$ \begin{align} |x_1y_1-x_2y_2|&=|(2\gamma\frac{x_1-x_2}{y_1-y_2}-y_2\frac{x_1-x_2}{y_1-y_2}+x_1)(y_1-y_2)|\\ &=|(2\gamma-y_2)(x_1-x_2)+x_1(y_1-y_2)|\\ &\leq|(2\gamma-y_2)||x_1-x_2|+x_1|y_1-y_2|\\ &\leq y_2|x_1-x_2|+|y_1-y_2|\\ &\leq|x_1-x_2|+|y_1-y_2| \end{align}

I think this is correct, but it seems way more tedious then it needs to be. So can someone:

a) verify that this is actually correct

b) Possibly explain how to do this shorter and more directly


You can use $\triangle$ -inequality: $|x_1y_1-x_2y_2|= |x_1y_1-x_1y_2 + x_1y_2 -x_2y_2| \leq |x_1y_1-x_1y_2|+|x_1y_2-x_2y_2|=|x_1||y_1-y_2|+|y_2||x_1-x_2|\leq |x_1-x_2|+|y_1-y_2|$

  • $\begingroup$ It seems that your proof is fine, but I still like mine ! $\endgroup$ – DeepSea Apr 3 '15 at 8:02
  • $\begingroup$ Haha thanks. I completely agree that your proof preferable. $\endgroup$ – user2520938 Apr 3 '15 at 8:05

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.